T cell receptor–induced phosphoinositide-3-kinase p110δ activity is required for T cell localization to antigenic tissue in mice - Jarmin, Sarah J.; David, Rachel; Ma, Liang; Chai, Jan-Guo; Dewchand, Hamlata; Takesono, Aya; Ridley, Anne J.; Okkenhaug, Klaus; Marelli-Berg, Federica M. (The Journal of Clinical Investigation, 2008)
The establishment of T cell–mediated inflammation requires the migration of primed T lymphocytes from the blood stream and their retention in antigenic sites. While naive T lymphocyte recirculation in the lymph and blood is constitutively regulated and occurs in the absence of inflammation, the recruitment of primed T cells to nonlymphoid tissue and their retention at the site are enhanced by various inflammatory signals, including TCR engagement by antigen-displaying endothelium and resident antigen-presenting cells. In this study, we investigated whether signals downstream of TCR ligation mediated by the phosphoinositide-3-kinase (PI3K) subunit p110δ contributed to the regulation of these events. T lymphocytes from mice expressing catalytically inactive p110δ displayed normal constitutive trafficking and migratory responses to nonspecific stimuli. However, these cells lost susceptibility to TCR-induced migration and failed to localize efficiently to antigenic tissue. Importantly, we showed that antigen-induced T cell trafficking and subsequent inflammation was abrogated by selective pharmacological inhibition of PI3K p110δ activity. These observations suggest that pharmacological targeting of p110δ activity is a viable strategy for the therapy of T cell–mediated pathology.